Contaminants in the Urban Environment: Microplastics - Maia McGuire; Yun-Ya Yang; Ignacio A. Rodriguez-Jorquera; Gurpal S. Toor; Alexander J. Reisinger (EDIS)
This publication is part of a series titled Contaminants in the Urban Environment. This series is intended to give state and local government officials, soil and water scientists, consulting engineers, Extension agents, and citizens (1) a basic understanding of the occurrence, toxic effects and source of various contaminants in the environment and (2) provide guidance on ways to protect human and environmental health.